A new approach of rock tension-compression cyclic measurement. Issue 1 (20th February 2019) - Liu, J.; Wang, C.; Wu, Z.; Wang, L.; Xu, H.; Pei, J.; Deng, C.
Abstract : Based on the MTS815 rock mechanics test system, a new measurement setup was developed to study the tension-compression cyclic behaviour of rocks. The new measurement setup implements a completely reversed loading condition that is direct tensile stress loading and compressive stress loading. Based on the experimental observation, the developed measurement setup can be easily applied for investigating the tension-compression cyclic behaviour of rock material. It is capable of monitoring the microcracking process by combining the developed measurement setup and AE testing system. The axial misalignment of experimental setup and the cylinder rigidity are the main factors affecting the availability of the new measurement method. When using this approach, the axial lines of the testing machine, the developed measurement setup and the rock sample need to be aligned. The cylinder rigidity should be far greater than the stress level applied in the test.